1994
DOI: 10.1111/j.1439-0442.1994.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Hormone on Growth Performance, Haematology, Metabolites and Hormones in Iron‐Deficient Veal Calves*

Abstract: Summary Effects of subcutaneous (s.c.) administration of 50 μg/kg body weight of recombinant bovine growth hormone (rbGH) or saline were studied for 11 weeks in 40 intact male veal calves supplied 50 mg or 10 mg of iron (Fe)/kg of milk replacer (MR). Feed intake, average daily gain and growth: feed ratio were reduced in Fe‐deficient calves, but not significantly influenced by rbGH. Plasma Fe and haemoglobin concentration, red‐cell number and packed cell volume were decreased in Fe‐deficient calves (P < 0.05) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 43 publications
2
7
1
Order By: Relevance
“…anaemia presented a significant reduction in serum IGF-I compared to calves with optimal iron concentration on day 10. The results obtained in our study are similar to other studies that investigated metabolic and endocrine changes during iron deficiency in veal calves (Ceppi and Blum 1994;Blum and Hammon 1999;Podhorský et al 2007). The IGF-I status markedly depends on energy and protein intake, as also shown in calves (Hammon and Blum 1998;Blum and Baumrucker 2002).…”
Section: Indicatorssupporting
confidence: 91%
See 1 more Smart Citation
“…anaemia presented a significant reduction in serum IGF-I compared to calves with optimal iron concentration on day 10. The results obtained in our study are similar to other studies that investigated metabolic and endocrine changes during iron deficiency in veal calves (Ceppi and Blum 1994;Blum and Hammon 1999;Podhorský et al 2007). The IGF-I status markedly depends on energy and protein intake, as also shown in calves (Hammon and Blum 1998;Blum and Baumrucker 2002).…”
Section: Indicatorssupporting
confidence: 91%
“…Although the positive correlation provides no indication of cause and effect, we consider that sufficient iron is required for normal secretion of IGF-I. Indeed, in situations of iron deficiency in rats, iron is a critical determinant of IGF-I regulation (Tran et al 2012), and previous research has also shown that iron deficiency reduces GH-mediated IGF-I secretion (Ceppi and Blum 1994). Nevertheless, conversely to what was observed in the iron deficiency state, parenteral administration of iron in calves during the early postnatal period resulted in a rise of serum IGF-I concentrations (Moosavian et al 2010).…”
Section: Indicatorsmentioning
confidence: 91%
“…In all the sampling periods, the serum Fe was lower than the reference value of 10-29 μmol/L for adult cattle reported by Radostis et al (2000). According to the literature, calves with Fe deficiency present reduced insulin concentrations (Ceppi and Blum 1994). Glucose levels in this study were slightly higher than the reference values reported for adults (1.9-3.8 mmol/L; Radostis et al 2000) even if no statistical differences were detected among sampling periods.…”
Section: Discussioncontrasting
confidence: 68%
“…There was a marked growth response to the administration of iron even in calves that were fed hay and grain in addition to milk [15,16]. It seems that sufficient iron is needed for normal appetite, secretion of IGF-I and tri-iodothyronine, and glucose utilization [20,27,28].…”
Section: Discussionmentioning
confidence: 99%